PERAN ORANG TUA DALAM MEMOTIVASI BELAJAR PESERTA DIDIK (Kajian tentang proses pembelajaran di era pandemi covid-19 di kelas VII MTs NEGERI 1 Pasuruan) - Siti Maisaroh; Maskuri Maskuri; Mohammad Muslim (VICRATINA, 2021)
The objectives of this study are: 1) To find out the efforts of parents to motivate students' learning in relation to the learning process in the era of the covid 19 pandemic in class VII MTs NEGERI 1 Pasuruan, 2) To find out the model of parents motivating students' learning in relation to the learning process in this era.  covid 19 pandemic in class VII MTs NEGERI 1 Pasuruan, 3) To find out student learning outcomes in relation to the learning process in the era of the covid 19 pandemic in class VII MTs NEGERI 1 Pasuruan.  This study uses a qualitative research that is a case study.  Researchers used data collection instruments with the process of observation, interviews, documentation.  The results of this study are 1) the efforts of parents in motivating students who are still closely related to the role of parents such as guiding their children, educating their children, accompanying their children's learning, fulfilling their children's needs, giving love and attention to their children.  2) parental models in motivating students include a) approach model that is between parents and children having good closeness by maintaining communication with children or with other businesses.  b) exemplary models, namely parents become role models in the eyes of children by always getting used to doing good things as a form of teaching children.  c) a motivator model, namely parents motivate children with things that make children motivated.  d) a model of law application, namely parents punish children who make mistakes, this is a warning to children not as parental revenge.  3) the results of parents after motivating students are a) Children are more enthusiastic in learning activities, b) Achieve good grades with high learning enthusiasm, c) Children are more disciplined in doing school assignments, d) There is a positive attitude change from children.